Shaping Modern Vaccines: Adjuvant Systems Using MicroCrystalline Tyrosine (MCT®) - Matthew D. Heath; Matthew D. Heath; Mona O. Mohsen; Mona O. Mohsen; Pieter-Jan de Kam; Thalia L. Carreno Velazquez; Simon J. Hewings; Simon J. Hewings; Matthias F. Kramer; Matthias F. Kramer; Thomas M. Kündig; Martin F. Bachmann; et al. (Frontiers in Immunology, 2020)
The concept of adjuvants or adjuvant systems, used in vaccines, exploit evolutionary relationships associated with how the immune system may initially respond to a foreign antigen or pathogen, thus mimicking natural exposure. This is particularly relevant during the non-specific innate stage of the immune response; as such, the quality of this response may dictate specific adaptive responses and conferred memory/protection to that specific antigen or pathogen. Therefore, adjuvants may optimise this response in the most appropriate way for a specific disease. The most commonly used traditional adjuvants are aluminium salts; however, a biodegradable adjuvant, MCT®, was developed for application in the niche area of allergy immunotherapy (AIT), also in combination with a TLR-4 adjuvant—Monophosphoryl Lipid A (MPL®)—producing the first adjuvant system approach for AIT in the clinic. In the last decade, the use and effectiveness of MCT® across a variety of disease models in the preclinical setting highlight it as a promising platform for adjuvant systems, to help overcome the challenges of modern vaccines. A consequence of bringing together, for the first time, a unified view of MCT® mode-of-action from multiple experiments and adjuvant systems will help facilitate future rational design of vaccines while shaping their success.